Evaluation of the Relationship Between Systemic Immune-Inflammatory Index and Morning Blood Pressure Surge in Newly Diagnosed Essential Hypertension Patients - Muhammet Salih Ateş; Fikret Keleş (Ahi Evran Medical Journal)
Purpose: This study aims to explore the relationship between the Systemic Immune-Inflammatory Index (SII) and Morning Blood Pressure Surge (MBPS) in patients with newly diagnosed essential hypertension.